Teacher-Led Initiatives in Supporting Learner Empowerment among Malay Tertiary Learners (Malaysian Journal of Learning and Instruction, 2014)
Purpose â€“ Learner empowerment or learner autonomy is regarded by some theorists as the self-propelled, sole effort of the learner. However, in creating self-directed learners who are empowered to learn, the role of significant others such as the instructor is imperative. This study shows how a committed lecturer can play an instrumental role in facilitating self-directed learning among learners. Methodology â€“ Learner autonomy in vocabulary learning was successfully facilitated among a group of Malay tertiary learners pursuing a Business Studies course in Malaysia. This qualitative study explored the lecturerâ€™s proactive efforts and initiatives in raising learnersâ€™ confidence in learning vocabulary. Data were collected through reflective in-depth interviews with the lecturer and learners at the end of every week for one month to obtain insights into their learning experiences. Findings â€“ The lecturerâ€™s pedagogical approaches of providing sufficient learning opportunities in class, teaching vocabulary in context, using vocabulary lists and direct methods, and building lessons spirally to reinforce learning made complex tasks become manageable and achievable. These efforts were well-commended by the learners in this study. The lecturer's conscious decisions, namely, encouraging collaborative learning tasks and not forcing reluctant speakers were guided by her awareness of the learnersâ€™ cultural background which impinged on their learning preferences, thus, creating a non-threatening learning environment. Significance â€“ This study establishes the case that learner empowerment is not teacherless learning but is fostered when the instructor is able to pitch the lesson at an appropriate level and create a conducive and positive learning environment to synchronise with the learnersâ€™ cultural traits.